We have been given an expression
. We are asked to find the solution to our given expression expressed as scientific notation.
Let us simplify our given expression.
Using exponent property
, we will get:
![8.5\times 2\times 10^3\times 10^5](https://tex.z-dn.net/?f=8.5%5Ctimes%202%5Ctimes%2010%5E3%5Ctimes%2010%5E5)
![17\times 10^{3+5}](https://tex.z-dn.net/?f=17%5Ctimes%2010%5E%7B3%2B5%7D)
![17\times 10^{8}](https://tex.z-dn.net/?f=17%5Ctimes%2010%5E%7B8%7D)
Now to write our answer in scientific notation, we need our 1st multiple between 1 and 10. So we will rewrite our expression as:
![1.7\times 10\times 10^{8}](https://tex.z-dn.net/?f=1.7%5Ctimes%2010%5Ctimes%2010%5E%7B8%7D)
![1.7\times 10^{1+8}](https://tex.z-dn.net/?f=1.7%5Ctimes%2010%5E%7B1%2B8%7D)
![1.7\times 10^{9}](https://tex.z-dn.net/?f=1.7%5Ctimes%2010%5E%7B9%7D)
Therefore, our required solution would be
.
Without resorting to L'Hopitâl's rule,
![\displaystyle\lim_{x\to9}\frac{x-9}{x^2-81}=\lim_{x\to9}\frac{x-9}{(x-9)(x+9)}=\lim_{x\to9}\frac1{x+9}=\frac1{18}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bx%5Cto9%7D%5Cfrac%7Bx-9%7D%7Bx%5E2-81%7D%3D%5Clim_%7Bx%5Cto9%7D%5Cfrac%7Bx-9%7D%7B%28x-9%29%28x%2B9%29%7D%3D%5Clim_%7Bx%5Cto9%7D%5Cfrac1%7Bx%2B9%7D%3D%5Cfrac1%7B18%7D)
With the rule, we get the same result:
![\displaystyle\lim_{x\to9}\frac{x-9}{x^2-81}=\lim_{x\to9}\frac1{2x}=\frac1{18}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bx%5Cto9%7D%5Cfrac%7Bx-9%7D%7Bx%5E2-81%7D%3D%5Clim_%7Bx%5Cto9%7D%5Cfrac1%7B2x%7D%3D%5Cfrac1%7B18%7D)
Answer:
Step-by-step explanation:
After one year
A=p(1+r/n)^nt
=2000(1+0.03/12)^12*1
=2000(1+0.0025)^12
=2000(1.0025)^12
=2000(1.0304)
=$2060.8
After two-years
A=p(1+r/n)^nt
=2060.8(1+0.03/12)^12*2
=2060.8(1+0.0025)^24
=2060.8(1.0025)^24
=2060.8(1.0618)
=$2188.157
After three years
A=p(1+r/n)^nt
=2188.157(1+0.03/12)^12*3
=2188.157(1+0.0025)^36
=2188.157(1.0025)^36
=2188.157(1.0941)
=$2394.063
The answer is B. 15 servings.
Answer:
x= -20, y= 10
Step-by-step explanation:
Label the two equations:
-7x -10y= 40 -----(1)
x= -2y -----(2)
Substitute (2) into (1):
-7(-2y) -10y= 40
Expand:
14y -10y= 40
Simplify:
4y= 40
Divide both sides by 4:
y= 40 ÷4
y= 10
Substitute y= 10 into (2):
x= -2y
x= -2(10)
x= -20